Voluntary termination of pregnancy in the context of decriminalized safe abortion: a longitudinal study on the availability, coverage, and utilization of services during 2016–2021 in Nampula province, northern Mozambique - Gilda Gondola Sitefane; Birgitta Essén; Osvaldo Loquiha; Khátia Munguambe; Esmeralda Mariano; William Ugarte; Pia Axemo (BMC Health Services Research)
Abstract Background Reducing maternal deaths is a critical public health concern. The Sustainable Development Goals (SDGs) aim to reduce maternal mortality globally to less than 70/100,000 live births by 2030. Mozambique has one of the highest maternal mortality rates in the world, at 233/100,000 live births. Of all maternal deaths, 11% are attributed to abortion. Mozambique decriminalized abortion in 2014 under certain conditions and approved clinical guidelines for service provision in 2016, aiming to reduce maternal deaths from unsafe abortion. This study assesses the availability, coverage, and utilization of facility-based voluntary termination of pregnancy (VTP) during the period 2016–2021 in Nampula province, northern Mozambique. Methods A descriptive quantitative study was performed, using secondary data analysis extracted from the national health monitoring information system (SIS-MA). Trends in the availability and utilization of VTP services were calculated from 2016 to 2021. The results were analysed while considering the geospatial distribution, coverage, and level of care of health facilities providing such services. Results Utilization of VTP services significantly increased by 77% (p < 0.001) and complications related to unsafe abortion decreased by 23.5% (p = 0.018) during 2016–2021. Conclusions Despite the significant improvement in service availability and utilization, the geographic distribution and population coverage of public health facilities providing services remains uneven and limited to semi-urban and urban areas, leaving unsafe abortion as the only option for women in rural areas. Despite these challenges, the results of this study reinforce scientific evidence that decriminalization of VTP and expansion of services may significantly improve access to and utilization of facility-based VTP, holding great potential for decreasing unsafe abortion-related complications and deaths.